The genetic basis of cognition. - Flint, J (1999)
The molecular characterization of single-gene disorders or chromosomal abnormalities that result in a cognitive abnormality (predominantly mental retardation) and of the genetic variants responsible for variation in intellectual abilities (such as IQ, language impairment and dyslexia) is expected to provide new insights into the biology of human cognitive processes. To date this hope has not been realized. Success in finding mutations that give rise to mental retardation has not been matched by advances in our understanding of how genes influence cognition. In contrast, the use of engineered mutations in mice to study models of learning and memory has cast new light on the molecular basis of memory. A comparison of studies of human and mouse mutations indicates the limitations of current genetic approaches to the understanding of human cognition. It is essential to interpret a mutation's effect within a well-characterized neural system; mutations can be used to define gene function only when the mutation has an effect on a system whose constituents form a serial causal chain, such as the molecular components of a signal transduction pathway. Typically, however, genetic mutations with a cognitive and behavioural phenotype are characterized by specific effects on different systems whose inter-relationships are unknown. Genetic approaches are currently limited to exploring neuronal function; it is not yet clear whether they will throw light on how neuronal connections give rise to cognitive processes. We need a much greater integration of different levels of understanding of cognition in order to exploit the genetic discoveries. In short, a rapprochement between molecular and systems neuroscience is required.